2021
DOI: 10.1111/jocs.15687
|View full text |Cite
|
Sign up to set email alerts
|

Use of longitudinal rigid sternal fixation in prevention and treatment of wound complications among high‐risk patients after cardiac surgery

Abstract: Background Traditionally, wire cerclage closure has been used to reapproximate the sternum after cardiac surgery. Recent evidence suggests that rigid sternal fixation may reduce the risk of wound complications. The aim of this study was to analyze our 10‐year experience with longitudinal rigid sternal fixation (LRSF) for prevention and treatment of wound complications in high‐risk patients. Methods We reviewed data from cardiac surgical database of patients who underwent LRSF, and compared their outcomes with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In most institutions like ours, single stainless-steel wires are used for sternum closure where the sutures are passed around the sternal body and through the manubrium or sternum body. The optimal number of single wires is not known [ 18 , 19 ], but Friberg et al demonstrated that the use of fewer than six wires rather than seven or more increased the rate of sternal wound infection from 0.4 to 4.2% [ 20 ]. Cadaveric studies have indicated increased stability of the sternum by using double wires, especially in obese patients, and a more recent review and meta-analysis illustrated the same [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most institutions like ours, single stainless-steel wires are used for sternum closure where the sutures are passed around the sternal body and through the manubrium or sternum body. The optimal number of single wires is not known [ 18 , 19 ], but Friberg et al demonstrated that the use of fewer than six wires rather than seven or more increased the rate of sternal wound infection from 0.4 to 4.2% [ 20 ]. Cadaveric studies have indicated increased stability of the sternum by using double wires, especially in obese patients, and a more recent review and meta-analysis illustrated the same [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…14 Highrisk patients are likely to experience postsurgical complications such as mediastinitis, sternum healed with deformity, sternal nonunion or sternal dehiscence. [15][16][17] Mediastinitis was one of the most lethal complications after cardiac surgery, and an overall mortality between 10% and 47% has been reported, which need extensive surgical debridement and long-term reconstruction. 18 These serious complications highlight the importance of a proper sternal closure device in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…The initial hospitalization costs, examination costs, treatment costs, total healthcare costs at 6 months and 12 months for all high-risk sternotomy patients is summarized in table 4. NRSP group had greater costs associated with their hospitalization compared with WC group($22,459 [19,469] vs $20,067 [17,,610], p¡0.001), driven primarily by the initial costs of NRSP. There was a non-significant trend in the costs of pharmacy, ICU, laboratory and imaging with or without NRSP(p¿0.05).…”
Section: Healthcare Costmentioning
confidence: 97%
“…Unfortunately, patients undergoing open thoracic/cardiac surgery had the highest rate of prolonged opioid use compared with other surgical cohorts ( 12 ). Others and we believe that improving the usual surgical techniques of the chest closing will minimize the risk of postoperative neuropathic pain ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%